2021
DOI: 10.3389/fcell.2021.634405
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Rat Cortical Development Induced by Ventricular Injection of rHMGB1 Mimics the Pathophysiology of Human Cortical Dysplasia

Abstract: Cortical dysplasia (CD) is a common cause of drug-resistant epilepsy. Increasing studies have implicated innate immunity in CD with epilepsy. However, it is unclear whether innate immune factors induce epileptogenic CD. Here, we injected recombinant human high mobility group box 1 (rHMGB1) into embryonic rat ventricles to determine whether rHMGB1 can induce epileptogenic CD with pathophysiological characteristics similar to those of human CD. Compared with controls and 0.1 μg rHMGB1-treated rats, the cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“… 8 These results suggested that HMGB1 may trigger seizures by inflammation pathways. 9 Lipopolysaccharide (LPS) is an effective inducer of inflammatory signaling, exacerbating inflammatory factors in peripheral and central systems of mice. 10 A noticeable increase in the severity of epileptic seizures and a decrease in the latency were observed in pilocarpine‐induced epilepsy model mice with LPS pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 These results suggested that HMGB1 may trigger seizures by inflammation pathways. 9 Lipopolysaccharide (LPS) is an effective inducer of inflammatory signaling, exacerbating inflammatory factors in peripheral and central systems of mice. 10 A noticeable increase in the severity of epileptic seizures and a decrease in the latency were observed in pilocarpine‐induced epilepsy model mice with LPS pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive high mobility group box 1(HMGB1), a rich nuclear and cytoplasmic protein in mammalian cells, was released after cell death or through active secretion, further resulted in inflammation 8 . These results suggested that HMGB1 may trigger seizures by inflammation pathways 9 . Lipopolysaccharide (LPS) is an effective inducer of inflammatory signaling, exacerbating inflammatory factors in peripheral and central systems of mice 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that chronic neuroinflammation with the CD47 and CD200 signaling pathways was activated in FCD brain samples 8 . Moreover, Toll‐like receptors (TLRs) and high‐mobility group box 1 (HMGB1) are upregulated in neurons and glial cells in FCDIIb and TSC 9,10 . HMGB1 belongs to the damage‐associated molecular patterns (DAMPs) and promotes the upregulation of downstream inflammatory factors in epilepsy, including nuclear factor‐κB (NF‐κB), interleukin‐1β (IL‐1β), and tumor necrosis factor‐α (TNF‐α) 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Moreover, Toll‐like receptors (TLRs) and high‐mobility group box 1 (HMGB1) are upregulated in neurons and glial cells in FCDIIb and TSC. 9 , 10 HMGB1 belongs to the damage‐associated molecular patterns (DAMPs) and promotes the upregulation of downstream inflammatory factors in epilepsy, including nuclear factor‐κB (NF‐κB), interleukin‐1β (IL‐1β), and tumor necrosis factor‐α (TNF‐α). 11 In addition, glucocorticoid therapy has achieved the prevention and treatment of epilepsy and epileptic encephalopathy by directly inhibiting the expression and release of IL‐1β and TNF‐α, 12 , 13 but has serious side effects (such as hypertension and osteoporosis).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that chronic neuroin ammation with the CD47 and CD200 signaling pathways was activated in FCD brain samples (Sun et al, 2016). Moreover, toll-like receptors (TLRs) and high-mobility group box 1 (HMGB1) are upregulated in FCDIIb and TSC (Zhang et al, 2018;Yang et al, 2021). HMGB1 belongs to the damage-associated molecular patterns (DAMPs) and upregulates downstream in ammatory factors in epilepsy, including nuclear factor kappa-B (NF-κB), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) (Wang et al, 2018).…”
mentioning
confidence: 98%